ARB dibandingkan non-ARB dalam Menurunkan Komplikasi Kardiovaskular pada Pasien Hipertensi dengan Risiko Tinggi: Laporan Berbasis Bukti - Alvin Nursalim; Yoga Yuniadi (Jurnal Kardiologi Indonesia, 2012)
Background: High risk hypertensive patients have an increased risk of developing cardiovascular complication. It is better to use a proven cardio protective drugs to reduce blood pressure in high risk hypertensive patients. Angiotensin II receptor Blocker (ARB) is one type of antihyper-tensive drugs with cardioprotective effect for hypertensive patients withoutother risk factor. Whether cardioprotective effect of ARB also apply for a more specific population such as high risk hypertensive patients need to be investigated.Aim: To determine the efficacy of ARB compared to non-ARBs in preventing cardiac event in a more specific population, such as high risk hypertensive patients.Methods: A search was conducted on PubMed and Cochrane. The selection of title and abstract was done using inclusion and exclusion criterias. Three original articles were found and used as the evidence tor the clinical question. The selected studies were critically appraised for validity, importance and applicability.Result: According to Sawada et al, the blood pressure lowering effect was similar between valsartan and non-ARB groups. The cardiovascular events in valsartan group is lower compared to non-ARB groups (relative risk: 0.54, 95% confidence interval 0.4-0.7, p< 0.001). The administration of valsartan as compared to non-ARB, also reduce the occurence of angina pectoris (Relative risk: 0.52, 95% Confidence Interval 0.31–0.86, P=0.01058). Cohn JN et al showed that there was no significant differences in the candesartan group in terms of total death and primary endpoints. The only significant finding in this article was the lower rate of diabetes mellitus in the candesartan group.Conclusion: Valsartan, as compared to non-ARB, reduce cardic event in high risk hypertensive patients.